Reimagining Australia via disability and media: Representation, access and digital integration - Kent, Michael; Ellis, Katie; Hollier, S.; Burns, S.; Goggin, G. (University of Barcelona, 2018)
This paper takes up pressing, yet sorely neglected, questions of disability and media to argue for a reimagining of Australia to be more inclusive of this group. To do so, we outline theoretical approaches to a reimagining of disability in society and culture. We then identify and debate the lessons from disability and media studies that help us to reimagine Australia. In particular, we focus on what we describe as the three key media models of disability in Australia—representation, access and digital inclusion. A key aim throughout this paper is to include the insights of people with disabilities themselves using the media in contemporary Australia. Our reimagining of Australia via disability and media exposes both the ambivalence taken towards disability in contemporary Australia as well as the potential for change.